2017
DOI: 10.1111/and.12928
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localisation of RXFP3 in human spermatozoa and impact of INSL7 on sperm functions

Abstract: Insulin-like peptide 7 (INSL7) or relaxin-3 is a member of the insulin superfamily that is recently discovered. This hormone interacts with relaxin family peptide receptor 3 (RXFP3). Although recent studies of INSL7 have focused on its function in the brain as a neuropeptide, spermatozoa may be a candidate target of INSL7 due to its detection in testes and contains binding sites. Therefore, this study aims to analyse the expression and localisation of RXFP3 on human spermatozoa and to assess the effect of INSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Relaxin-1 is also believed to exist as circulatory peptide in the circulation ( Bathgate et al, 2013 ), but the function of the relaxin-1 in humans and higher primates is mostly unclear. Relaxin-3 is the most recently identified member of the relaxin family and is primarily expressed in the brain of mammals ( Heidari et al, 2018 ). In our study, we first tested the vasoactive function of all three relaxins in mouse mesenteric arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxin-1 is also believed to exist as circulatory peptide in the circulation ( Bathgate et al, 2013 ), but the function of the relaxin-1 in humans and higher primates is mostly unclear. Relaxin-3 is the most recently identified member of the relaxin family and is primarily expressed in the brain of mammals ( Heidari et al, 2018 ). In our study, we first tested the vasoactive function of all three relaxins in mouse mesenteric arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Ou et al (2020) carried out a transcriptome analysis on spermatogonial stem cells (SSCs) and reported that LRRC34 was highly expressed in mouse SSCs and was essential for in vitro SSC proliferation. RXFP3 was identified to be differentially expressed in human sperm and was likely diminished in spermiogenesis (Heidari et al, 2018). Furthermore, other studies suggested PPP2R2B and PCK1 as candidate genes affecting the semen quality traits in livestock (Huang et al, 2016;Gao et al, 2019).…”
Section: Genome-wide Association Studiesmentioning
confidence: 98%